W staropolskiej kuchni i przy polskim stole - Lemnis, Maria; Vitry, Henryk (Warszawa : Wydawn. Interpress, 1989)
A cook book with traditional Polish recipes and a description of some traditions associated with food.
Keywords: Cooking, Polish